Credit Scoring and the Quality of Business Credit During the Crisis. (9th April 2017) - Demma, Cristina
Abstract : The Great Recession produced a sharp worsening of credit quality for banks and firms alike. In this context, this paper investigates whether in Italy during the period 2008–2011 credit quality was higher for the banks that had adopted credit scoring techniques before the crisis and actually incorporated them into their loan evaluation process. To this end, I use a unique dataset built by merging information about banks organization variables drawn from the Regional Bank Lending Survey, the main banks' balance sheet indicators and data on non‐performing loans drawn from the Italian Central Credit Register and from banks' supervisory reports to the Bank of Italy. The main finding is that, after controlling for other supply factors, during the financial crisis the banks that relied more heavily on credit scoring models had higher‐quality loans to non‐financial companies. This result is consistent with the thesis that scoring models mitigated the negative impact of the crisis by enhancing banks' screening ability. However, the positive effect is significant only for loans granted to large firms; for smaller firms, the absence of a significant effect could be explained by the greater importance traditionally attached to other means of assessing their creditworthiness, mainly soft information.